2008
DOI: 10.1111/j.1365-2869.2008.00638.x
|View full text |Cite
|
Sign up to set email alerts
|

Disagreement between subjective and actigraphic measures of sleep duration in a population‐based study of elderly persons*

Abstract: Summary Sleep duration is an important concept in epidemiological studies. It characterizes a night’s sleep or a person’s sleep pattern, and is associated with numerous health outcomes. In most large studies, sleep duration is assessed with questionnaires or sleep diaries. As an alternative, actigraphy may be used, as it objectively measures sleep parameters and is feasible in large studies. However, actigraphy and sleep diaries may not measure exactly the same phenomenon. Our study aims to determine disagreem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
265
3
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 347 publications
(304 citation statements)
references
References 43 publications
(97 reference statements)
28
265
3
3
Order By: Relevance
“…Of studies that identified an association between extreme sleep durations and worse cognitive function, each ascertained subjective sleep duration via participant self report. This is interesting, considering the fact that previous studies have reported a discrepancy between subjective vs. objective assessments of sleep duration; indeed, there is some indication that older adults with perceived or actual problems with sleep quality may report more extreme sleep durations [44,81] . A minority of studies in this review considered sleep-related variables other than sleep duration (i.e.…”
Section: Discussionmentioning
confidence: 93%
“…Of studies that identified an association between extreme sleep durations and worse cognitive function, each ascertained subjective sleep duration via participant self report. This is interesting, considering the fact that previous studies have reported a discrepancy between subjective vs. objective assessments of sleep duration; indeed, there is some indication that older adults with perceived or actual problems with sleep quality may report more extreme sleep durations [44,81] . A minority of studies in this review considered sleep-related variables other than sleep duration (i.e.…”
Section: Discussionmentioning
confidence: 93%
“…While there is evidence that self-reported mass may be underestimated, they are not considered significant enough to affect the results 32) . Self-reported sleep length and actigraphic sleep recordings have been shown to be well correlated 33) but it is the case that the accuracy depends on the cognitive and functional abilities of participants 34) Third, it may be the case that other confounders were present that we could not control (eg. energy intake and physical activity).…”
Section: Discussionmentioning
confidence: 97%
“…The use of PSG should be considered, because participants with insomnia often misestimate their actual sleep status. 65,66 However, in consideration of the cost of polysomnography, and the additional burden for the enrolled elderly, we chose not to use PSG. A second limitation is the lack of follow-up durations and the small sample size.…”
Section: Discussionmentioning
confidence: 99%